Market Orientation and Innovation Performance: Mediating Effects of Customer Engagement in SMEs - Ni Made Wahyuni; I Made Sara (Universitas Hayam Wuruk Perbanas, 2020)
This study's objective is to develop an innovation performance model based on the role of market orientation and customer engagement. Market-oriented practices through customer engagement will enable companies to achieve innovation performance. This research was conducted on small and medium enterprises (SMEs) engaged in manu-facturing in Bali. A conceptual model was developed to determine the mediating role of customer engagement in the relationship between market orientation and innovation performance. The research design used was cross-sectional. Quantitative data were collected from 242 respondents by distributing questionnaires to managers and own-ers of manufacturing SMEs in Bali. The model was tested using Partial Least Square (PLS). The results of this study show that market orientation has a significant positive effect on innovation performance, market orientation has a positive effect on customer engagement, customer engagement has a positive effect on innovation performance, and customer engagement partially mediates the relationship between market orienta-tion and innovation performance. The results of this study are expected to be able to increase managers' insight and understanding of the mechanisms of how market ori-entation and customer engagement can contribute to innovation performance in ex-port-oriented SMEs.